This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: .. +x(n)*h(1) ... y(2*n1) = x(n)*h(n) Therefore y[n] = [2 10 11 22 26 1 9 9 6] For the 4th edition with x[n] = [1 5 3 0 3] and h[n] = [2 0 5 3 2], then Y c [n] = [6 3 4 12 48 24 5 3 11 2 3]. Problem 3: Problem 4: Proving Eq. 5.116 Checking if eq. 5.115 holds we have. .. y c [n] = [6 7 6 5] Y c [k] = [24 j2 0 j2] = therefore. .. ( 36 + 49 +36 +25) = .25(576 + 4 + 0 + 4) 146 = 146, and Eq. 5.115 holds. Problem 5: G[k] = [4, 1j, 2, 1+j] (equation 5.29) (equation 5.31) Therefore. .....
View
Full
Document
This note was uploaded on 12/04/2010 for the course ECE 134 taught by Professor York during the Fall '08 term at UCSB.
 Fall '08
 York

Click to edit the document details